Efektivitas Metode Interaktif terhadap Pemahaman Jaringan Komputer Siswa SMK melalui Penguatan Literasi Digital - Safira Azhari; Salsabila Khoirunnisa; Niken Dwi Rianti; Tian Nurani (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
The rapid development of information and communication technology demands the education sector to strengthen digital literacy, particularly in mastering computer networks. Observations at SMK Taruna Bakti Baturraden revealed that 10th-grade students face difficulties in understanding basic network concepts such as topology, hardware, IP addresses, and the use of Cisco Packet Tracer. This study aims to measure the effectiveness of interactive teaching methods in improving students' understanding. The activities were carried out through stages including observation, module preparation, delivery of interactive materials, and evaluation. The learning process involved participatory presentations, discussions, and hands-on simulations. Evaluation was conducted using quizzes and student reflections. The results showed a significant increase in students' understanding of networking concepts and enthusiasm in learning network technologies. Furthermore, the activity enhanced students' digital literacy through a practical approach and the use of simulation applications. These findings indicate that interactive teaching methods are effective in improving computer network comprehension and can serve as a replicable digital literacy-based learning model in other vocational schools.